Polyimide adhesive and its preparation method and application
By using a hydroxyl polyimide porous film in the flexible copper clad plate to impregnate the fluorine-containing resin emulsion, the fluororesin-modified polyimide bond is formed, which solves the problem of difficult balance of dielectric characteristics and flexibility, and achieves low dielectric constant, low dielectric loss and excellent flexibility of the copper clad plate.
Patent Information
- Application Number
- CN202011128719.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-10-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2040-10-20
AI Technical Summary
The prior art is difficult to achieve a balance between dielectric properties and flexibility in flexible copper clad plates, especially because fluororesin particles are difficult to disperse uniformly in the polyimide precursor solution, which affects the flexibility of copper clad plates.
By preparing a porous hydroxy polyimide film and impregnating it with a fluororesin emulsion, a fluororesin-modified polyimide bond is formed. This method improves the bonding force between fluororesin and polyimide by the formation of hydrogen bonds, and improves the interface wetting property during the thermal recombination process, and enhances the bonding force with copper foil.
It realizes the low dielectric constant, low dielectric loss and excellent flexibility of copper clad plate, and is suitable for flexible printed circuit board field.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of circuit boards, and relates to flexible copper-clad laminates, and specifically to a fluororesin-modified polyimide adhesive with low dielectric constant and low dielectric loss, a preparation method thereof, and a copper-clad laminate with excellent flexibility comprising the adhesive. Background Art
[0002] Flexible printed circuits (FPC) have been widely used in electronic products due to their advantages of being light, thin, and flexible. Flexible copper clad laminates (FCCL) are the basic materials for producing FPCs, and polyimide (PI) films are widely used in FCCL substrate materials due to their high thermal stability, low hygroscopicity, and good mechanical properties.
[0003] With the development of electronic products towards high performance and short, small, light and thin, higher requirements are put forward for the performance and production process of circuit board (PCB), especially the base material of FCCL has low dielectric constant and low dielectric loss. Due to the low dielectric property of fluororesin, and excellent electrical insulation, friction resistance and weather resistance, the prior art discloses the use of fluororesin to modify polyimide to improve its dielectric properties. The general modification method is to add fluororesin as micropowder to the precursor solution of polyimide, but because the synthesis of polyimide precursor solution is generally carried out in an oily solvent, the fluororesin particles are very easy to agglomerate, and the difficulty is easy to disperse evenly, which is not conducive to the improvement of the flexibility of copper clad plate. For this reason, CN107429028A first prepares the dispersion of fluororesin, and then mixes the dispersion with the precursor solution of polyimide, solidifies, and obtains the polyimide film modified by fluororesin. However, due to the addition of auxiliary agents such as surfactants and dispersants in the dispersion of fluororesin, the dielectric properties of metal laminates are affected. Summary of the invention
[0004] In view of the problem that it is difficult to achieve a balance between dielectric properties and flexibility in copper clad laminates in the prior art, the present invention provides a copper clad laminate having low dielectric constant, low dielectric loss and excellent flexibility.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] In one aspect, the present invention provides a method for preparing a polyimide adhesive, comprising:
[0007] S1, providing a hydroxy polyimide porous membrane prepared from hydroxy diamine and aromatic dianhydride;
[0008] S2. Immerse the hydroxy polyimide porous membrane in the fluorine-containing resin emulsion and dry it to obtain a polyimide bond.
[0009] In the above-mentioned preparation method provided by the present invention, on the one hand, the hydrogen in the hydroxyl group in the polyimide porous membrane can form a hydrogen bond with the fluorine in the fluororesin, thereby increasing the bonding force between the fluororesin and the polyimide porous membrane; on the other hand, during the thermal composite process of the copper foil, the partially exposed hydroxyl groups can improve the interfacial wettability and increase the bonding force with the copper foil.
[0010] According to some embodiments of the present invention, the hydroxy diamine is at least one of 4,6-diamino-1,3-resorcinol, 2,2-bis(3-amino-4-hydroxy-1,1,13,3,3-hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 3,3'-diamino-4,4-dihydroxydiphenyl ether, 3,3'-diamino-4,4-dihydroxydiphenyl sulfide, 3,3'-diamino-4,4-dihydroxybiphenyl, 3,3'-diamino-4,4-dihydroxydiphenylmethane, and 3,3'-diamino-4,4-dihydroxydiphenyl sulfone.
[0011] In addition to the hydroxydiamines listed above, other hydroxydiamines commonly used in the art can also be used in the present invention.
[0012] In the preparation method of the present invention, the aromatic dianhydride is preferably a fluorine-free aromatic dianhydride. Although the fluorine-containing aromatic dianhydride can further increase the compatibility of the fluorine-containing resin and the polyimide porous membrane, due to the characteristics of the fluorine atom itself, it will also reduce the adhesion of the resulting bonded body to the copper foil. Therefore, if the fluorine-containing aromatic dianhydride is used, its amount is not easy to be too much. Preferably, the molar ratio of the non-fluorine-containing aromatic dianhydride to the fluorine-containing aromatic dianhydride is 0.95-0.85:0.05-0.15.
[0013] The structure of the non-fluorine-containing aromatic dianhydride is not particularly limited, and any non-fluorine-containing aromatic dianhydride commonly used in the art can be used in the present invention. For example, 4,4'-biphenyl ether dianhydride, 4,4'-terephthalic anhydride, pyromellitic anhydride, 3,3',4,4'-triphenyl ether tetracarboxylic anhydride, 3,3',4,4'-benzophenone tetracarboxylic anhydride, 3,3',4,4'-diphenyl ether tetracarboxylic anhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic anhydride, 3,3',4,4'-biphenyl tetracarboxylic anhydride, etc. can be cited. The above-mentioned non-fluorine-containing aromatic dianhydrides listed can be used alone or in combination.
[0014] According to some embodiments of the present invention, the non-fluorinated aromatic dianhydride is at least one of 4,4'-biphenyl ether dianhydride, 4,4'-diphenylene oxide diphthalic anhydride, pyrophthalic anhydride, 3,3',4,4'-triphenyl ether tetracarboxylic anhydride, 3,3',4,4'-benzophenone tetracarboxylic anhydride, 3,3',4,4'-diphenyl ether tetracarboxylic anhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic anhydride, and 3,3',4,4'-biphenyl tetracarboxylic anhydride.
[0015] The structure of the fluorinated aromatic dianhydride is not particularly limited, and any fluorinated aromatic dianhydride commonly used in the art can be used in the present invention. For example, 6,6'-bis-trifluoromethyl-2,3,3',4'-biphenyltetracarboxylic acid dianhydride, 4,4'-hexafluoroisopropylphthalic anhydride, triptycene-4,5-bis-trifluoromethyl-2,3,6,7-tetracarboxylic acid dianhydride, 4,4'-(hexafluoroisopropyl) diphthalic acid dianhydride, 2,3,6,7-tetracarboxylic acid-9,9-bis(trifluoromethyl)xanthene dianhydride, 1,4-bis(trifluoromethyl) The fluorine-containing aromatic dianhydrides listed above may be used alone or in combination.
[0016] According to some embodiments of the present invention, the fluorinated aromatic dianhydride is 6,6'-di-trifluoromethyl-2,3,3',4'-biphenyltetracarboxylic dianhydride, 4,4'-hexafluoroisopropylphthalic anhydride, triptycene-4,5-ditrifluoromethyl-2,3,6,7-tetracarboxylic dianhydride, 4,4'-(hexafluoroisopropyl) diphthalic anhydride, 2,3,6,7-tetracarboxylic dianhydride, At least one of bis(trifluoromethyl)xanthene dianhydride, 1,4-bis(trifluoromethyl)-2,3,5,6-benzenetetracarboxylic dianhydride, 1,4-bis(3.4-dicarboxytrifluorophenoxy)tetrafluorophthalic dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]hexafluoropropane dianhydride, 1,4-difluoropyromellitic dianhydride, 2,2-bis(3,4-dicarboxyphthalic dianhydride)hexafluoropropane, 1,4-bis(3,4-dicarboxytrifluorophenoxy)tetrafluorophthalic dianhydride, and 2,2'-difluoro-4,4'-biphenyl dianhydride.
[0017] Preferably, the porous membrane is prepared by mixing the hydroxydiamine and the aromatic dianhydride in a molar ratio of 1:1.
[0018] The method for preparing the hydroxypolyimide porous film is not particularly limited, and examples thereof include a template method, a phase transfer method, a non-solvent method, a porogen method, and the like.
[0019] According to some embodiments of the present invention, the thickness of the hydroxyl polyimide porous membrane is 5-100 μm, preferably 10-60 μm.
[0020] The pore size of the hydroxyl polyimide porous membrane should not be too small, which is not conducive to the impregnation of the fluorine-containing resin emulsion, resulting in unsatisfactory impregnation efficiency. According to some embodiments provided by the present invention, the pore size of the hydroxyl polyimide porous membrane is 1-100 μm, preferably 3-50 μm, and more preferably 5-20 μm.
[0021] According to some embodiments of the present invention, the porosity of the hydroxyl polyimide porous membrane is 30-95%, preferably 40-90%, and more preferably 50-85%.
[0022] According to some embodiments of the present invention, the fluorine-containing resin emulsion is at least one of polytetrafluoroethylene (PTFE) emulsion, polytetrafluoroethylene-perfluoroalkyl vinyl ether (PFA) emulsion, and perfluoroethylene propylene copolymer (FEP) emulsion, preferably PTFE emulsion.
[0023] The solid content of the fluorine-containing resin emulsion should not be too high, otherwise the viscosity will be too high, affecting the impregnation efficiency. According to some embodiments provided by the present invention, the solid content of the fluorine-containing resin emulsion is 30-75wt%.
[0024] The immersion temperature is not particularly limited and can be carried out at room temperature (20-35°C). If the solid content of the fluorine-containing resin emulsion is high and the viscosity is large, it can also be heated appropriately, for example, at 40-60°C.
[0025] The immersion time can be adjusted according to the porosity and pore size of the hydroxypolyimide porous membrane and the solid content of the fluorine-containing resin emulsion, and is not particularly limited.
[0026] Drying after impregnation is preferably performed in steps. According to some embodiments of the present invention, the drying conditions after impregnation are: drying at 50-120°C for 5-10 min, and drying at 180-250°C for 5-20 min.
[0027] According to some embodiments provided by the present invention, the content of fluorine-containing resin in the polyimide adhesive is 5-30wt%, preferably 10-25wt%. If the content of fluorine-containing resin is too low, the dielectric properties of the adhesive are not significantly improved, and if the content of fluorine-containing resin is too high, the adhesive properties will be adversely affected.
[0028] On the other hand, the present invention provides a polyimide bonded body obtained by the above preparation method, which has excellent dielectric properties and bonding properties.
[0029] In another aspect, the present invention provides a copper-clad laminate comprising the polyimide adhesive and a method for manufacturing the same. The copper-clad laminate has excellent flexibility and can be applied to the field of flexible printed circuit boards.
[0030] The manufacturing method of the copper clad laminate comprises: laminating copper foil, polyimide adhesive and insulating film in sequence, and hot pressing to obtain the copper clad laminate.
[0031] Preferably, a copper foil made by a calendering method is used, and the thickness of the copper foil can be selected to be 5-100 μm, preferably 5-60 μm. According to actual needs, the copper foil can be roughened.
[0032] The insulating film is preferably a polyimide film.
[0033] Hot pressing conditions can be selected: 250-300℃ / 10-30min, 300-400℃ / 10-30min, hot pressing pressure 25-100Kg / cm 2 .
[0034] The present invention has the following technical effects:
[0035] In the preparation method provided by the present invention, a bonded body with excellent dielectric properties and bonding properties is obtained by impregnating a fluororesin emulsion with a hydroxyl polyimide porous membrane. On the one hand, the hydrogen in the hydroxyl group in the polyimide porous membrane can form a hydrogen bond with the fluorine in the fluororesin, thereby increasing the bonding force between the fluororesin and the polyimide porous membrane; on the other hand, during the thermal compounding process of the copper foil, the partially exposed hydroxyl group can improve the wettability of the interface and increase the bonding force with the copper foil. The copper clad laminate containing the bonded body has excellent flexibility and can be applied to the field of flexible printed circuit boards. DETAILED DESCRIPTION
[0036] Unless otherwise specified, all scientific and technological terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. All patents and publications related to the present invention are incorporated herein by reference in their entirety. The term "comprising" or "including" is an open expression, that is, including the contents specified in the present invention, but does not exclude contents in other aspects.
[0037] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. In the examples, if no specific conditions are specified, the conditions described in the specification or the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0038] Example 1
[0039] In this embodiment, the preparation method of the polyimide adhesive and the copper clad laminate is as follows:
[0040] (1) 3,3'-diamino-4,4-dihydroxydiphenyl sulfide and 4,4'-biphenyl ether dianhydride were prepared according to a molar ratio of 1:1 to prepare a hydroxy polyimide porous film with a thickness of 30 μm, an average pore size of 5 μm, and a porosity of 85%;
[0041] (2) impregnating the above-mentioned hydroxyl polyimide porous film with a PTFE emulsion having a solid content of 50 wt%, and then drying at 100° C. for 10 min and at 250° C. for 20 min to obtain a polyimide bond having a fluororesin content of 20 wt%;
[0042] (3) The 20 μm copper foil, the above-mentioned polyimide adhesive, and the 10 μm polyimide film were stacked together in sequence and placed in a hot press for hot pressing. The hot pressing procedure was: heating to 250°C and holding for 30 minutes, then heating to 380°C for 1 hour, holding for 30 minutes, and then cooling to room temperature. The hot pressing pressure was 65 Kg / cm 2 .
[0043] Example 2
[0044] In this embodiment, the preparation method of the polyimide adhesive and the copper clad laminate is as follows:
[0045] (1) 3,3'-diamino-4,4-dihydroxydiphenyl sulfide and 4,4'-biphenyl ether dianhydride were prepared according to a molar ratio of 1:1 to prepare a hydroxy polyimide porous film with a thickness of 30 μm, an average pore size of 5 μm, and a porosity of 85%;
[0046] (2) impregnating the above-mentioned hydroxyl polyimide porous film with a PTFE emulsion having a solid content of 70 wt%, and then drying at 100° C. for 10 min and at 250° C. for 20 min to obtain a polyimide bond having a fluororesin content of 30 wt%;
[0047] (3) The 20 μm copper foil, the above-mentioned polyimide adhesive, and the 10 μm polyimide film were stacked together in sequence and placed in a hot press for hot pressing. The hot pressing procedure was: heating to 250°C and holding for 30 minutes, then heating to 380°C for 1 hour, holding for 30 minutes, and then cooling to room temperature. The hot pressing pressure was 65 Kg / cm 2 .
[0048] Example 3
[0049] In this embodiment, the preparation method of the polyimide adhesive and the copper clad laminate is as follows:
[0050] (1) 3,3'-diamino-4,4-dihydroxydiphenyl sulfide and 4,4'-biphenyl ether dianhydride were prepared according to a molar ratio of 1:1 to prepare a hydroxy polyimide porous film with a thickness of 30 μm, an average pore size of 5 μm, and a porosity of 85%;
[0051] (2) impregnating the above-mentioned hydroxyl polyimide porous film with a PTFE emulsion having a solid content of 30 wt%, and then drying at 100° C. for 10 min and at 250° C. for 20 min to obtain a polyimide bond having a fluororesin content of 10 wt%;
[0052] (3) The 20 μm copper foil, the above-mentioned polyimide adhesive, and the 10 μm polyimide film were stacked together in sequence and placed in a hot press for hot pressing. The hot pressing procedure was: heating to 250°C and holding for 30 minutes, then heating to 380°C for 1 hour, holding for 30 minutes, and then cooling to room temperature. The hot pressing pressure was 65 Kg / cm 2 .
[0053] Example 4
[0054] In this embodiment, the preparation method of the polyimide adhesive and the copper clad laminate is as follows:
[0055] (1) 3,3'-diamino-4,4-dihydroxydiphenyl sulfide and 4,4'-biphenyl ether dianhydride were prepared according to a molar ratio of 1:1 to prepare a hydroxy polyimide porous film with a thickness of 20 μm, an average pore size of 8 μm, and a porosity of 50%;
[0056] (2) impregnating the above-mentioned hydroxyl polyimide porous film with a PTFE emulsion having a solid content of 50 wt%, and then drying at 100° C. for 10 min and at 250° C. for 20 min to obtain a polyimide bond having a fluororesin content of 12 wt%;
[0057] (3) The 20 μm copper foil, the above-mentioned polyimide adhesive, and the 10 μm polyimide film were stacked together in sequence and placed in a hot press for hot pressing. The hot pressing procedure was: heating to 250°C and holding for 30 minutes, then heating to 380°C for 1 hour, holding for 30 minutes, and then cooling to room temperature. The hot pressing pressure was 65 Kg / cm 2 .
[0058] Example 5
[0059] In this embodiment, the preparation method of the polyimide adhesive and the copper clad laminate is as follows:
[0060] (1) 3,3'-diamino-4,4-dihydroxydiphenyl sulfide, 4,4'-biphenyl ether dianhydride, and 2,2-bis(3,4-dicarboxylic acid phthalic anhydride)hexafluoropropane were prepared according to a molar ratio of 1:0.9:0.1, with a hydroxy polyimide porous film having a thickness of 30 μm, an average pore size of 5 μm, and a porosity of 85%;
[0061] (2) impregnating the above-mentioned hydroxyl polyimide porous film with a PTFE emulsion having a solid content of 50 wt%, and then drying at 100° C. for 10 min and at 250° C. for 20 min to obtain a polyimide bond having a fluororesin content of 21 wt%;
[0062] (3) The 20 μm copper foil, the above-mentioned polyimide adhesive, and the 10 μm polyimide film were stacked together in sequence and placed in a hot press for hot pressing. The hot pressing procedure was: heating to 250°C and holding for 30 minutes, then heating to 380°C for 1 hour, holding for 30 minutes, and then cooling to room temperature. The hot pressing pressure was 65 Kg / cm 2 .
[0063] Comparative Example 1
[0064] The present embodiment is different from the embodiment 1 in that the non-hydroxy diamine 4,4'-diaminodiphenyl ether is used to replace the 3,3'-diamino-4,4-dihydroxydiphenyl sulfide.
[0065] Performance Testing
[0066] The copper clad laminates prepared in Examples 1-5 and Comparative Example 1 were tested for dielectric properties, flexibility and peel strength. The test results are shown in Table 1.
[0067] Table 1
[0068]
[0069] It can be seen from the test data in Table 1 that, compared with the comparative example, the copper clad laminate including the polyimide adhesive prepared in the embodiment of the present invention has excellent dielectric properties and flexibility, and the polyimide adhesive has a strong bonding force with the copper foil. After adding fluorinated aromatic dianhydride, the peel strength decreases slightly, and the bonding force between the polyimide adhesive and the copper foil becomes weaker.
[0070] In the description of this specification, the description with reference to the terms "some embodiments", "other embodiments", "embodiment", "example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0071] Although the embodiments and examples of the present invention have been shown and described above, it is to be understood that the above embodiments and examples are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments and examples within the scope of the present invention.
Claims
1. A method for preparing a polyimide bond, characterized in that: include: S1, providing a hydroxy polyimide porous membrane prepared from hydroxy diamine and aromatic dianhydride; The hydroxy diamine is 3,3'-diamino-4,4-dihydroxy diphenyl sulfide; the aromatic dianhydride is 4,4'-biphenyl ether dianhydride; the thickness of the hydroxy polyimide porous membrane is 10-60 μm; the pore size of the hydroxy polyimide porous membrane is 5-20 μm; the porosity of the hydroxy polyimide porous membrane is 50-85%; S2, impregnating the hydroxy polyimide porous membrane with a fluorine-containing resin emulsion and drying the membrane to obtain a polyimide bond; The fluorine-containing resin emulsion is polytetrafluoroethylene emulsion; the solid content of the fluorine-containing resin emulsion is 30-75wt%; and the content of the fluorine-containing resin in the polyimide bond is 5-30wt%.
2. The method for preparing a polyimide bond according to claim 1, characterized in that: The drying comprises: drying at 50-120° C. for 5-10 min, and drying at 180-250° C. for 5-20 min.
3. The method for preparing a polyimide bond according to claim 1, characterized in that: In the polyimide adhesive, the content of the fluorine-containing resin is 10-25 wt %.
4. The polyimide bond obtained by the preparation method according to any one of claims 1 to 3.
5. A copper-clad laminate comprising the polyimide adhesive of claim 4.
Citation Information
Patent Citations
Nonaqueous dispersion containing fluorine-based resin, polyimide precursor solution composition containing fluorine-based resin, polyimide, polyimide film and adhesive composition for circuit boards, each using said polyimide precursor solution composition containing fluorine-based resin; and production methods thereof
CN107429028A
Method for preparing binder of polyimide of containing phenolic hydroxyl group
CN101003716A
A method and apparatus for preparing fluorinated coated polyimide films.
CN102266844A
Double-sided flexible copper clad laminate and its manufacturing method
CN102275341A